PREDICTION OF CONVERGENCE VALUES IN SHALLOW TUNNELS WITH VARIATIONS IN SUPPORT SYSTEMS FOR GOOD ROCK MASS CLASS (RMR = 61-80) - Adityo Avicena, Aulia
This study aims to analyze the deformation behavior of tunnels, particularly the horizontal displacement caused by excavation processes. Using the finite element method, the research evaluates the magnitude of horizontal convergence and horizontal strain occurring on the left and right walls of the tunnel. Horizontal displacement data was collected from monitoring points located 1 meter above the spring line, where rock movement and stress distribution are expected to be most significant. The analysis results show that the tunnel experiences significant horizontal convergence at several points, with the largest convergence value before support installation being 5.86 cm, and after support installation being 3.29 cm, at a depth of 60 meters. Based on the analysis of the support capacity curve diagram from Eurocode 2 (1992), the use of support system type 4 is recommended for depths up to 60 meters in shallow tunnels.